Optimization of aviation adjuvants based on wettability analysis for insecticide application on maize using UAV - Zang, Yu; Zhou, Zhiyan; Zang, Ying; Luo, Xiwen; Liao, Juan; Ming, Rui; Song, Cancan; Zi, Le; Jiang, Rui; Xiao, Hanxiang (International Journal of Agricultural and Biological Engineering, 2021)
Adjuvants can increase the control efficacy of diseases and insect pests by changing the physico-chemical properties of pesticides. Most of the aviation spray adjuvants are versions of ground adjuvants. Maize insecticide sprays with unmanned aerial vehicles (UAV), have problems such as relatively low droplet deposition rate and poor wettability. Hence, wettability research and optimization tests for aviation spray adjuvants are needed. The present study screened 12 spray adjuvants using physico-chemical property experiments. The adjuvants were applied to improve the droplet deposition and control efficacy in maize borers controlling by UAV. The selected spray adjuvants were Po2 (a hyperbranched polymer adjuvant) and VO3 (a vegetable oil adjuvant). Results showed that, (1) When Po2 was added in water-dispersible granules (WGs) at volume rate of 12 L/hm2, the dynamic surface tension (DST) of WGs was decreased by 37.41%, and the maize leaves were covered by droplets 100%, the droplet deposition was increased by 104% and maize borer control was increased by 46%; (2) VO3 decreased the surface tension of ultra-low-volume (ULV) formulation by 12.02% and the maize leaves were covered by droplets 100%. The effect of VO3 on improving the droplet deposition and control efficacy at 12 L/hm2 with ULV was not significant. Thus, the addition of aviation spray adjuvant to improve the wettability of WGs significantly improved the droplet deposition and control efficacy but it had no significant effect on the ULV formulation.Keywords: unmanned aerial vehicles, spray adjuvants, wettability, maize insecticide applicationDOI: 10.25165/j.ijabe.20211405.6605Citation: Zang Y, Zhou Z Y, Zang Y, Luo X Y, Liao J, Ming R, et al. Optimization of aviation adjuvants based on wettability analysis for insecticide application on maize using UAV. Int J Agric & Biol Eng, 2021; 14(5): 11–18.